Community Empowerment Through Appropriate Technology: Wastewater Treatment Plant (WWTP) Program in Home-Made Batik Industry at Ngawi, Indonesia - Winarko Winarko; Bambang Hadi Sugito; Sri Utami; Sari Luthfiyah (Frontiers in Community Service and Empowerment, 2022)
The increasing number of companies and the number of batik productions in the Ngawi region is directly proportional to the amount of wastewater produced and thus poses a burden on the environment as the overflow of wastewater is absorbed from the production process. The results of the laboratory analyses showed that the values for TSS, color, COD, BOD, total ammonia, oil, and grease exceeded the quality standards. Prevention of pollution from wastewater is done through community empowerment. Community empowerment aims to realize the development of Appropriate Technology for Wastewater Treatment Plants (WWTP) and the prevention of Wastewater Pollution to the Environment Around Small and Medium Enterprises (UKM) Griya Batik Widi Nugraha, Ngawi Regency. The benefit of community empowerment is to provide experience for other Batik Wastewater Treatment Plant (WWTP) development programs. Community empowerment at UKM Griya Batik Widi Nugraha Ngawi uses methods of document collection, site surveys, preparation of processing systems, training, and demonstrations. The target group of community empowerment activities at Griya Batik Widi Nugraha Ngawi are the owner of Griya Batik Widi Nugraha Ngawi, batik workers at Griya Batik Widi Nugraha Ngaw, workers in the dyeing and washing process, administrators of Ngawi Batik Association and construction workers. Results of Community Empowerment of UKM Griya Batik Widi Nugraha Workers and Surroundings Together with the academic community of Poltekkes Kemenkes Surabaya, appropriate technology was built for a wastewater treatment plant (WWTP) with a capacity of 1,464.5 liters per day, which is still safe for UKM Griya Batik Widi Nugraha Ngawi Regency. The stages of wastewater treatment are pre-treatment, secondary treatment, tertiary treatment, and storage of the final product. The results of the functional tests based on effluent samples from the final treatment showed that the treatment plant was able to reduce the levels of TSS, color, COD, BOD, total ammonia, oil, and grease that exceeded the quality standard to meet the quality requirements as per the Minister of Environment and Forestry Regulation No. P.16/MENLAHK /SETJEN/KUM.1/2019. These results provide benefits for UKM Griya Batik Widi Nugraha to prevent pollution and can use treated water as a source of fish pond water and watering the garden. It is recommended that community empowerment can be continued by other SMEs that have the potential to dispose of wastewater from production activities and pollute the environment through the use of appropriate technology (TTG) research results by lecturers or students so that they do not stop as intakes.